The Contribution of KH. M. Hasyim Asy'ari in the Development of Hadith Thought and Islamic Education in Indonesia - Khumaedi, Memed (LP2M IAI Miftahul Ulum Pamekasan, 2024)
This study examines the contribution of KH. Hasyim Asy'ari in the development of hadith thought and Islamic education in Indonesia. The background of this research is rooted in the importance of hadith as a source of Islamic teachings that influence the morals and ethics of society. The issue addressed is how KH. Hasyim Asy'ari's thoughts can be integrated into the current Islamic education curriculum. The method used is qualitative, involving text analysis and interviews with experts in Islamic education. The research findings indicate that KH. Hasyim Asy'ari's thoughts on integrating hadith values in education can create a holistic learning environment that is relevant to the needs of modern society. This research is expected to provide new insights into the development of a hadith-based educational curriculum that can adapt to contemporary challenges.